ANALISIS SISTEM PENGENDALIAN INTERNAL TERHADAP PEMBERIAN KREDIT PADA UEK-SP XYZ PEKANBARU - Dian Saputra; Khofifah Kultsum Salamah (UIR Press, 2024)
Entrepreneurship is a profession that is widely practiced by various levels of society which is certainly supported by a lot of capital to achieve success. It is common knowledge that a handful of people borrow credit to get capital as a first step in starting a business. Bad credit is a phenomenon that often occurs when credit lending is carried out. This research was conducted to see and assess the effectiveness of the internal control system in granting credit at one of the community institutions, UEK-SP XYZ. This research uses descriptive data analysis with COSO's Internal Control System component as the main theory. The results of this study indicate that the components of integrity and ethical values are still not well implemented due to the implementation of several policies that increase the number of bad debts, duplicate positions, inappropriate placement of functions based on the last education of staff and ineffective monitoring.